2020
DOI: 10.1093/neuros/nyaa381
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Neurostimulation of the Mesial Temporal White Matter in Bilateral Temporal Lobe Epilepsy

Abstract: BACKGROUND Responsive neuromodulation (RNS) is a treatment option for patients with medically refractory bilateral mesial temporal lobe epilepsy (MTLE). A paucity of data exists on the feasibility and clinical outcome of hippocampal-sparing bilateral RNS depth lead placements within the parahippocampal white matter or temporal stem. OBJECTIVE To evaluate seizure reduction outcomes with at least a 1-yr follow-up in individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…However, this was not associated with a difference in outcome. This finding is consistent with other reports that have found RNS to be efficacious even if the contacts do not lie precisely within the SOZ or if the SOZ is not well defined 2,13,14 . There may still be value to approximating the target structures, as the volume of tissue activated by slightly off‐target leads may include the target structure or its input and output pathways.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, this was not associated with a difference in outcome. This finding is consistent with other reports that have found RNS to be efficacious even if the contacts do not lie precisely within the SOZ or if the SOZ is not well defined 2,13,14 . There may still be value to approximating the target structures, as the volume of tissue activated by slightly off‐target leads may include the target structure or its input and output pathways.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with other reports that have found RNS to be efficacious even if the contacts do not lie precisely within the SOZ or if the SOZ is not well defined. 2,13,14 There may still be value to approximating the target structures, as the volume of tissue activated by slightly off-target leads may include the target structure or its input and output pathways. A previous report found that seizure control correlates with proximity of stimulator contacts to the subiculum, which is adjacent to the EC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on ictal mapping using SEEG has shown that a greater percentage of patients with good surgical outcomes had stimulation induced seizures compared to the poor outcome cohort 31 ; a finding that motivates the use of depth electrodes to interrogate seizure networks. The utility in quantifying white matter coverage may also be relevant in patients who are candidates for neuromodulation therapy to control their seizures using responsive neurostimulation, as recent evidence indicates that placement of leads and stimulation in the parahippocampal or temporal stem white matter may more effectively target the epileptic network in temporal lobe epilepsy (TLE) without sacrificing recording ability 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosing refractory epilepsy remains a tedious task. While several researchers investigated refractory epilepsy to diagnose and reveal possible causes (3,4), the main cause remains unknown, and doctors are yet to determine why some patients are receptive to medicine and others not.…”
Section: Introductionmentioning
confidence: 99%